Field studies on the influence of rainfall intensity, vegetation cover and slope length on soil moisture infiltration on typical watersheds of the Loess Plateau, China. Issue 25 (6th October 2020) - He, Zimiao; Jia, Guodong; Liu, Ziqiang; Zhang, Zhenyao; Yu, Xinxiao; Xiao, Peiqing
Abstract: Soil moisture is a key process in the hydrological cycle. During ecological restoration of the Loess Plateau, soil moisture status has undergone important changes, and infiltration of soil moisture during precipitation events is a key link affecting water distribution. Our study aims to quantify the effects of vegetation cover, rainfall intensity and slope length on total infiltration and the spatial variation of water flow. Infiltration data from the upper, middle and lower slopes of a bare slope, a natural grassland and an artificial shrub grassland were obtained using a simulated rainfall experiment. The angle of the study slope was 15° and rainfall intensity was set at 60, 90, 120, 150, and 180 mm/hr. The effect these factors have on soil moisture infiltration was quantified using main effect analysis. Our results indicate that the average infiltration depth (ID) of a bare slope, a grassland slope and an artificial shrub grassland slope was 46.7–73.3, 60–80, and 60–93.3 cm, respectively, and average soil moisture storage increment was 3.5–5.7, 5.0–9.4, and 5.7–10.2 mm under different rainfall intensities, respectively. Heavy rainfall intensity and vegetation cover reduced the difference of soil infiltration in the 0–40 cm soil layer, and rainfall intensity increased surface infiltration differences on the bare slope, the grassland slope and the artificial shrub grassland slope. Infiltration was dominated by rainfall intensity, accounting for 63.03–88.92%. As rainfall continued, the contribution of rainfall intensity to infiltration gradually decreased, and the contribution of vegetation cover and slope length to infiltration increased. The interactive contribution was: rainfall intensity * vegetation cover > vegetation cover * slope length > rainfall * slope length. In the grass and shrub grass slopes, lateral flow was found at a depth of 23–37 cm when the slope length was 5–10 m, this being related to the difference in soil infiltration capacity between different soil layers formed by the spatial cross‐connection of roots. Abstract : The effects and contribution of vegetation cover rainfall intensity and slope length on vertical and spatial changes of soil water infiltration were quantified. The existence of saturated lateral runoff was found and it was considered that the spatial interleaving of root system also formed the difference of soil infiltration capacity between different soil layers, which provided the possibility of lateral runoff. Rainfall intensity, vegetation canopy interception and slope length confluence provided sufficient water supply for the occurrence of lateral runoff.